Asymmetric water-permeable nano generator based on copper oxide and preparation method of asymmetric water-permeable nano generator
By regulating the microstructure of copper nanowires and the asymmetric load structure of foam, the material regulation problems and stability problems in existing water penetration power generation devices are solved, and an efficient water penetration nanogenerator is realized, which can self-drive the conversion of low-grade energy into electrical energy.
Patent Information
- Application Number
- CN202411710042.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
AI Technical Summary
In existing water permeability power generation devices, the high specific surface area and active sites of the material cannot be accurately regulated, which makes it difficult to improve the electrical signal, and the chemical properties and stability of the material are poor, so it cannot work for a long time.
Copper nanowires were synthesized by polyol reduction method and lightly oxidized in a solution environment to regulate the microstructure of the nanowires. The suction filtration loading technology is used to load different lightly oxidized nanowires on the left and right ends of the foam to build an asymmetric structure. Then calcined at high temperature in an air atmosphere, and the glycerol steam gradient reduction was performed in vacuum to regulate the carrier concentration difference to obtain an asymmetric water permeability nanogenerator based on copper oxide.
By regulating the microstructure and carrier concentration differences of copper oxide nanowires, the power production performance of water-permeable nanogenerators is significantly improved, and the self-driven low-grade energy conversion function is realized.
Smart Images

Figure CN119561412A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fluid power generation, and in particular relates to an asymmetric water permeation nanogenerator based on copper oxide and a preparation method thereof. Background Art
[0002] With the development of industrialization and the continuous growth of energy consumption, the rational development of energy and the balance of supply and demand need to be solved urgently, and the strategy of "increasing revenue and reducing expenditure" is considered to be one of the effective strategies to meet this challenge. Among them, "increasing revenue" refers to the active development and efficient use of diversified energy resources, and "reducing expenditure" emphasizes saving energy and improving energy utilization efficiency. Against the background of generally tight global electricity supply, how to use various types of energy more efficiently, especially converting low-grade energy that has not yet been fully utilized into electrical energy, is regarded as one of the key technologies for optimizing the energy structure and alleviating the contradiction between electricity supply and demand. This is of great significance to promoting global energy transformation and sustainable development.
[0003] Water penetration is ubiquitous in nature, such as grains swelling when they absorb water, and nutrients in animals entering the blood through thin films. Using self-driven water penetration to generate electricity has become a hot topic in current research, and the development of functional materials is crucial. Usually, liquid osmosis power generation devices require the use of micro-nano materials with high specific surface area and rich active sites, mainly including nanocarbon, layered double hydroxides, and conductive polymers. However, the surface charge of carbon materials cannot be precisely controlled, resulting in difficulty in significantly increasing the generated electrical signal. Layered double hydroxides have a certain degree of water solubility, so they cannot work for a long time in a liquid environment. Conductive polymers have poor chemical properties and stability, and are prone to decomposition after long-term use.
[0004] Therefore, it is necessary to find new functional materials and construct high-performance water permeation power generation devices by regulating the micromorphology of materials and optimizing the device structure to meet practical application needs. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides an asymmetric water permeation nanogenerator based on copper oxide and a preparation method thereof. The present invention first synthesizes copper nanowires by a polyol reduction method, and then lightly oxidizes the copper nanowires in a solution environment to regulate the microstructure of the nanowires. Using the suction filtration loading technology, the nanowires with different light oxidation levels are loaded on the left and right ends of the foam respectively to construct an asymmetric structure and form a specific surface area difference. After high-temperature calcination in an air atmosphere, glycerol vapor gradient reduction is carried out in a vacuum to increase the difference in carrier concentration at both ends, thereby obtaining an asymmetric water permeation nanogenerator based on copper oxide.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing an asymmetric water permeation nanogenerator based on copper oxide, the specific steps are as follows: dispersing the synthesized copper nanowires in an ethanol solution, adding an oxidant, and mildly oxidizing for a certain period of time to obtain Cu / Cu x O nanowires; the foam was immersed in a copper salt solution for a certain period of time to make it copper-philic; after drying, the foam (6cm×1cm×2mm) was divided into two equal areas, and the Cu / Cu with different mild oxidation was separated by filtration. x O nanowires are loaded on the micro-skeleton at the left and right ends of the foam according to the principle of morphological asymmetry; after being fully dried, they are placed in an air atmosphere for high-temperature calcination; after cooling to room temperature, they are placed vertically in a vacuum tank and gradient reduced using the difference in glycerol vapor concentration to obtain an asymmetric water permeation nanogenerator based on copper oxide.
[0008] Furthermore, the preparation steps of the copper nanowires are as follows: copper salt is used as a precursor, dissolved in a polyol solvent, continuously stirred and heated to T1, after adding a directing agent, slowly heated to T2, and after a certain reaction time, a brick red solution is obtained, and the copper nanowires are collected by centrifugation washing three times with n-hexane.
[0009] Furthermore, the copper salt is at least one of basic copper carbonate, copper sulfate, copper chloride, copper nitrate, copper acetate, copper citrate, and cuprous chloride; the polyol is at least one of ethylene glycol, glycerol, 1,2-propylene glycol, 1,4-butanediol, and polyethylene glycol; and the directing agent is at least one of oleylamine, oleic acid, potassium bromide, ammonium bromide, and ammonium chloride.
[0010] Furthermore, the amount of the copper salt is 1-15 mmol; the volume of the polyol is 30-100 ml; the amount of the copper salt to the directing agent is 1:1-10:1; the T1 range is 30-70°C, the T2 range is 160-220°C, the heating rate is 5-10°C / min, and the reaction time is 40-100 min.
[0011] Furthermore, the oxidant is at least one of ammonium persulfate, potassium permanganate, hydrogen peroxide, dilute hydrochloric acid, dilute sulfuric acid, citric acid and oxalic acid; the concentration of the oxidant is 1-20wt%, the volume is 5-30ml; and the oxidation time is 1-8h.
[0012] Furthermore, the foam is one of polyurethane foam, polyethylene foam, melamine foam, and ethylene-vinyl acetate copolymer foam.
[0013] Furthermore, the copper salt solution for soaking the foam is one of copper sulfate, cupric chloride, cuprous chloride and copper acetate, the concentration is 0.1-0.5 mol / l, and the soaking time is 1-6h.
[0014] Furthermore, the temperature of the high temperature calcination in the air atmosphere is 250-450° C., and the time is 2-5 hours.
[0015] Furthermore, the volume of the gradient reduced glycerol is 0.5-4 ml, the reduction temperature is 180-240° C., and the reduction time is 30-100 min.
[0016] On the other hand, the present invention also provides an asymmetric water permeation nanogenerator based on copper oxide, which is prepared by the above method.
[0017] Compared with the prior art, the advantages of the present invention are as follows:
[0018] The present invention discloses an asymmetric water permeation nanogenerator based on copper oxide and a preparation method thereof. The prepared water permeation nanogenerator is based on the ion voltaic effect, generates electrical signals through the difference in carrier concentration between dry and wet areas, and can convert low-grade energy into electrical energy through self-driving without external energy input. The present invention selects nano semiconductors as functional materials, regulates the microscopic composition of nanowires through a method of mild oxidation-high temperature oxidation-gradient reduction, and constructs a nanogenerator with a three-dimensional asymmetric structure by utilizing the original structure of the foam matrix. The regulation of the copper oxide microstructure and the asymmetric integrated design effectively improve the power generation performance, and can be widely used in the field of self-powered sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.
[0020] Figure 1 is the open circuit voltage generated by the nanogenerator prepared in Example 1 when infiltrated with a 0.1 mol / l NaCl solution;
[0021] Figure 2 is the short-circuit current generated by the nanogenerator prepared in Example 1 when infiltrated with a 0.1 mol / l NaCl solution;
[0022] Figure 3 is the slightly oxidized Cu / Cu in Example 1 x SEM image of O nanowire a;
[0023] Figure 4 is the slightly oxidized Cu / Cu in Example 1 x SEM image of O nanowire b;
[0024] Figure 5 This is a SEM image of the nanowires in Comparative Example 1 that were not lightly oxidized and directly calcined at high temperature;
[0025] Figure 6 This is the SEM image of the melamine foam loaded with nanowires in Example 1. DETAILED DESCRIPTION
[0026] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:
[0027] Example 1
[0028] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide, comprising the following steps:
[0029] First, prepare copper nanowires: use 2 mmol of copper salt as a precursor, dissolve it in a mixed solvent of 30 ml of ethylene glycol and 5 ml of polyethylene glycol, continue stirring for 30 minutes and heat to 45°C. After adding 1 mmol of oleylamine, slowly heat to 198°C. After reacting for 60 minutes, a brick-red solution is obtained. The copper nanowires are collected by centrifugation and washing three times with n-hexane.
[0030] 200 mg of copper nanowires were dispersed in 20 ml of ethanol solution, and 5 ml of 1 wt% citric acid and 5 ml of 1 wt% hydrogen peroxide were added. After mild oxidation for 2 h, Cu / Cu x Another 200 mg of copper nanowires were dispersed in 20 ml of ethanol solution, and 5 ml of 1 wt% citric acid and 5 ml of 1 wt% hydrogen peroxide were added. After mild oxidation for 4 h, Cu / Cu x O nanowire b. Melamine foam was immersed in 0.2 mol / l cuprous chloride solution for 3 h to make it copper-philic. After drying, the melamine foam (6 cm × 1 cm × 2 mm) was divided into two equal areas. The Cu / Cu with different mild oxidation was filtered out. x O nanowires a and b are loaded on the micro-skeleton at the left and right ends of the foam, respectively. After being fully dried, it is calcined at 350°C in an air atmosphere. After cooling to room temperature, the foam is placed vertically in a vacuum tank with end a touching the bottom, and reduced with 2 ml of glycerol vapor at 220°C for 40 minutes to obtain an asymmetric water permeation nanogenerator based on copper oxide.
[0031] Add 60 μL of NaCl solution (0.1 M) to the end of the melamine foam and measure the open circuit voltage and short circuit current. Figure 1 and Figure 2 As shown, the generated voltage is about 0.61V and the current is about 21.6μA.
[0032] The asymmetric water permeation nanogenerator based on copper oxide of the present invention is based on the ion voltaic effect. The magnitude of the open circuit voltage and the short circuit current are jointly determined by the microstructure (morphology and composition) of the nano copper oxide and the macrostructure (integrated and asymmetric design) of the device. If any conditions change, the power generation performance of the device will change.
[0033] Example 2
[0034] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide, comprising the following steps:
[0035] First, prepare copper nanowires: 3 mmol of copper sulfate was used as a precursor, dissolved in a mixed solvent of 50 ml of ethylene glycol and 5 ml of propylene glycol, stirred continuously for 1 hour and heated to 35°C. After adding 0.3 mmol of ammonium chloride, the temperature was slowly raised to 180°C. After reacting for 40 minutes, a brick-red solution was obtained. The copper nanowires were collected by centrifugation and washing three times with n-hexane.
[0036] 200 mg of copper nanowires were dispersed in 30 ml of ethanol solution, 15 ml of 4 wt% ammonium persulfate was added, and Cu / Cu was obtained after mild oxidation for 4 h. x Another 200 mg of copper nanowires were dispersed in 30 ml of ethanol solution, and 15 ml of 8 wt% ammonium persulfate was added. After mild oxidation for 8 h, Cu / Cu x O nanowire b. The polyurethane foam was immersed in 0.1 mol / l copper sulfate solution for 5 h to make it copper-philic. After drying, the polyurethane foam (6 cm × 1 cm × 2 mm) was divided into two equal areas. The Cu / Cu with different mild oxidation was filtered out. x O nanowires a and b are loaded on the micro-skeleton at the left and right ends of the foam, respectively. After being fully dried, it is calcined at 300°C in an air atmosphere. After cooling to room temperature, the foam is placed vertically in a vacuum tank with end a touching the bottom, and reduced with 4 ml of glycerol vapor at 180°C for 90 minutes to obtain an asymmetric water permeation nanogenerator based on copper oxide.
[0037] 60 μL of NaCl solution (0.1 M) was added to the end of the polyurethane foam, and the open circuit voltage and short circuit current generated were measured. Finally, the voltage generated was about 0.52 V and the current was about 10.2 μA.
[0038] Example 3
[0039] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide, comprising the following steps:
[0040] First, prepare copper nanowires: 1 mmol of cuprous chloride and 1 mmol of cupric chloride mixture were used as precursors, dissolved in 40 ml of ethylene glycol solvent, stirred continuously and heated to 50°C, 2 mmol of oleic acid was added, and the temperature was slowly raised to 200°C. After reacting for 50 minutes, a brick-red solution was obtained, which was washed three times by centrifugation with n-hexane to collect the copper nanowires.
[0041] 200 mg of copper nanowires were dispersed in 20 ml of ethanol solution, and 10 ml of 5 wt% dilute hydrochloric acid was added. After mild oxidation for 3 h, Cu / Cu x Another 200 mg of copper nanowires were dispersed in 20 ml of ethanol solution, and 10 ml of 5 wt% dilute hydrochloric acid was added. After mild oxidation for 6 h, Cu / Cu x O nanowire b. Melamine foam was immersed in 0.3 mol / l copper chloride solution for 4 h to make it copper-philic. After drying, the melamine foam (6 cm × 1 cm × 2 mm) was divided into two equal areas. The Cu / Cu with different mild oxidation was filtered out. x O nanowires a and b are loaded on the micro-skeleton at the left and right ends of the foam, respectively. After being fully dried, it is calcined at 400°C in an air atmosphere. After cooling to room temperature, the foam is placed vertically in a vacuum tank with end a touching the bottom, and reduced with 1 ml of glycerol vapor at 200°C for 30 minutes to obtain an asymmetric water permeation nanogenerator based on copper oxide.
[0042] 60 μL of NaCl solution (0.1 M) was added to the end of the melamine foam, and the open circuit voltage and short circuit current generated were measured. Finally, the voltage generated was about 0.43 V and the current was about 8.7 μA.
[0043] Comparative Example 1
[0044] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide, and the steps are different from those in Example 1: no mild oxidation is performed after the copper nanowires are synthesized; 60 μL of NaCl solution (0.1 M) is added to the end a of the melamine foam, and the generated open circuit voltage and short circuit current are measured. Finally, the open circuit voltage is 0.47 V and the short circuit current peak is 12.9 μA.
[0045] This is because mild oxidation can remove the organic coating attached to the surface of the original copper nanowires, which helps the subsequent high-temperature calcination process to occur more evenly on the surface of the nanowires, effectively increasing the roughness of the nanowire surface, and the rich active sites are more conducive to the reaction at the solid-liquid interface, such as Figure 3 and Figure 4 After the copper nanowires are directly calcined at high temperature, the surface of the generated copper oxide nanowires is relatively smooth, as shown in Figure 5 As shown, the specific surface area is relatively small, resulting in low power generation performance.
[0046] Comparative Example 2
[0047] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide. The difference from Example 1 is that the melamine foam is not pre-treated by copper salt immersion. 60 μL of NaCl solution (0.1 M) is added to the end a of the melamine foam, and the open circuit voltage and short circuit current generated are measured. Finally, the open circuit voltage is 0.5 V and the short circuit current peak is 13.9 μA.
[0048] This is because the copper ions in the copper salt solution can interact with the functional groups (such as hydroxyl, carboxyl, etc.) on the surface of the foam to form chemical bonds, thereby enhancing the adhesion between the copper nanowires and the foam. Figure 6 This interaction helps prevent the nanowires from falling off the foam during subsequent processing. Without soaking the foam in copper salt, it is difficult for the nanowires to attach to the foam microskeleton and they are only loaded on the surface of the foam, resulting in poor power generation performance.
[0049] Comparative Example 3
[0050] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide. The difference from the embodiment 1 is that the same Cu / Cu x O nanowires, without constructing asymmetric structures. 60 μL of NaCl solution (0.1 M) was added to the end of the melamine foam with a higher degree of reduction, and the open circuit voltage and short circuit current were measured. Finally, the open circuit voltage was 0.35 V and the short circuit current peak was 7.4 μA.
[0051] This is because the specific surface area of the materials loaded on the left and right ends of the foam is the same, and there is no obvious difference in the contact area of the solid-liquid interface during liquid penetration, resulting in lower power generation performance.
[0052] Comparative Example 4
[0053] This embodiment provides a method for preparing an asymmetric water permeation nanogenerator based on copper oxide, which is different from that in Example 1 in that: after high-temperature calcination, no subsequent glycerol vapor gradient reduction is performed, 60 μL of NaCl solution (0.1 M) is added to the end a of the melamine foam, and the generated open circuit voltage and short circuit current are measured. Finally, the open circuit voltage is 0.43 V and the short circuit current peak is 9.9 μA.
[0054] This is because reduction will cause defective structures in the nanowires, and the defects will lead to the generation of additional defect energy levels. This energy level, as a carrier recombination center, will change the carrier concentration of nano-copper oxide, thereby increasing the difference in carrier concentration at both ends of the dry and wet areas, effectively improving the conductivity.
[0055] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0056] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0057] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing an asymmetric water permeation nanogenerator based on copper oxide, characterized in that: The specific steps are as follows: the synthesized copper nanowires are dispersed in an ethanol solution, an oxidant is added, and Cu / Cu is obtained after a certain period of mild oxidation. x O nanowires; soak the foam in a copper salt solution for a certain period of time to make it copper-philic; after drying, divide the foam into two equal areas, and use the suction filtration method to separate the slightly oxidized Cu / Cu x O nanowires are loaded on the micro-skeleton at the left and right ends of the foam according to the principle of morphological asymmetry; after being fully dried, they are placed in an air atmosphere for high-temperature calcination; after cooling to room temperature, they are placed vertically in a vacuum tank and gradient reduced using the difference in glycerol vapor concentration to obtain an asymmetric water permeation nanogenerator based on copper oxide.
2. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The preparation steps of the copper nanowires are as follows: copper salt is used as a precursor, dissolved in a polyol solvent, continuously stirred and heated to T1, after adding a directing agent, the temperature is slowly raised to T2, and a brick red solution is obtained after a certain reaction time, and the copper nanowires are collected by centrifugation washing three times with n-hexane.
3. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The copper salt is at least one of basic copper carbonate, copper sulfate, copper chloride, copper nitrate, copper acetate, copper citrate, and cuprous chloride; the polyol is at least one of ethylene glycol, glycerol, 1,2-propylene glycol, 1,4-butanediol, and polyethylene glycol; and the directing agent is at least one of oleylamine, oleic acid, potassium bromide, ammonium bromide, and ammonium chloride.
4. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The amount of the copper salt is 1-15 mmol; the volume of the polyol is 30-100 ml; the amount ratio of the copper salt to the directing agent is 1:1-10:1; the T1 range is 30-70°C, the T2 range is 160-220°C, the heating rate is 5-10°C / min, and the reaction time is 40-100 min.
5. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The oxidant is at least one of ammonium persulfate, potassium permanganate, hydrogen peroxide, dilute hydrochloric acid, dilute sulfuric acid, citric acid and oxalic acid; the concentration of the oxidant is 1-20wt%, the volume is 5-30ml; and the oxidation time is 1-8h.
6. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The foam is one of polyurethane foam, polyethylene foam, melamine foam and ethylene-vinyl acetate copolymer foam.
7. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The copper salt solution for soaking the foam is one of copper sulfate, copper chloride, cuprous chloride and copper acetate, the concentration is 0.1-0.5 mol / l, and the soaking time is 1-6 hours.
8. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The temperature of the high temperature calcination in the air atmosphere is 250-450° C., and the time is 2-5 hours.
9. The method for preparing an asymmetric water permeation nanogenerator based on copper oxide according to claim 1, characterized in that: The volume of the gradient reduced glycerol is 0.5-4 ml, the reduction temperature is 180-240° C., and the reduction time is 30-100 min.
10. An asymmetric water permeation nanogenerator based on copper oxide, characterized in that: The method is prepared by any one of claims 1 to 9.